Priority Scale For Determining Physical Maintenance Using the AHP Method At Klego Dam, Boyolali Regency - Hardiansah Hardiansah; I Putu Artama Wiguna (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to evaluate the safety and performance of the Klego Dam in Boyolali, Central Java, using a quantitative descriptive method with primary and secondary data. The research stages involve damage analysis, adjustment of the dam's physical conditions to the research location, and analysis of the current conditions. Maintenance handling is prioritised using the Analytical Hierarchy Process (AHP) method, focusing on spillway channels, turbulent flow, and serrated sections. The physical conditions are analysed to determine the dam's status in 2022. The AHP program prioritises based on performance, safety, cost, damage, and component function. The results of the prioritisation scale for maintenance handling of the Klego Dam are as follows: (1) completing dam instrumentation with a priority matrix value of 0.646; (2) dam infrastructure repair with a value of 0.223; (3) completing the dam's emergency system with a value of 0.132.